Peer critique as a signature pedagogy in writing studies. (July 2017) - Heinert, Jennifer
In this essay, the author connects research on student learning in writing studies with the theory of signature pedagogies first presented by Shulman in 2005. In particular, the author unpacks how peer critique (also called peer review) develops the habits of mind of the discipline articulated in the "Framework for Success in Postsecondary Writing"(Hansen, 2012). By looking through the lens of Shulman's structural definition of signature pedagogies, the author shows how peer critique develops the "habits of head, hand, and heart" of writing studies (Ciccone, 2009).